2009
DOI: 10.1111/j.1540-6288.2009.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

One Man Two Hats: What's All the Commotion!

Abstract: We examine performance in publicly listed U.K. companies over a period that encompasses the issuance of the Cadbury Committee's Code of Best Practice, which calls for the abolition of the combined CEO/COB position. We find that companies splitting the combined CEO/COB position to conform to the Code's requirement did not exhibit any absolute or relative improvement in performance when compared to various peer-group benchmarks. We do not necessarily scoff at mandated board structures, but the evidence suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…However, our multivariate tests find no evidence that CEO duality has a significant effect on firm performance. Our evidence casts doubt on the notion that firms changing from duality to non-dual Vance (1978); Sullivan (1988); Rechner & Dalton (1989); Leng (2004); Dahya, Galguera-Garcia &Bommel (2009) andYasser (2011) where they reported that duality is not significant to firm performance.…”
Section: Resultscontrasting
confidence: 57%
“…However, our multivariate tests find no evidence that CEO duality has a significant effect on firm performance. Our evidence casts doubt on the notion that firms changing from duality to non-dual Vance (1978); Sullivan (1988); Rechner & Dalton (1989); Leng (2004); Dahya, Galguera-Garcia &Bommel (2009) andYasser (2011) where they reported that duality is not significant to firm performance.…”
Section: Resultscontrasting
confidence: 57%
“…Finkelstein and D'Aveni (1994) postulate that the choice of leadership structure reflects the board's effort to balance entrenchment avoidance with unity of command. Empirical evidence is, however, mixed on the relation between leadership structure and firm performance (Brickley et al, 1997;Dahya, 2004;Rechner & Dalton, 1991). In spite of this inconclusive evidence, shareholder activists, institutional investors, and regulators hold the view that the CEO should not serve in the role of board chairperson.…”
Section: Governance and Corporate Survivalmentioning
confidence: 98%
“…Others, however, remain unconvinced (Baliga, Moyer, & Rao, 1996;Dahya et al, 2009;Dalton et al, 2008;Dey, Engel, & Liu, 2009;Faleye, 2007;Finkelstein & D'Aveni, 1994). Dahya et al (2009), for example, concluded that the abandonment of the combined CEO/ chairperson of the board position "appears to be wide of the mark" (p. 179).…”
Section: Board Leadership Structurementioning
confidence: 99%
“…Dahya et al (2009), for example, concluded that the abandonment of the combined CEO/ chairperson of the board position "appears to be wide of the mark" (p. 179). Faleye (2007), too, suggests that insistence to "separate CEO and chairman duties may be counterproductive" and "may not produce the desired results" (p. 256).…”
Section: Board Leadership Structurementioning
confidence: 99%
See 1 more Smart Citation